Educating helping professionals for encouragement of interethnic tolerance and reconciliation - Čorkalo, Dinka (1999)
The reconstruction of social communities is one of the most difficult task in the post-war resettlement process in Croatia. The question to be asked is how to help people who were on the opposite sides during the conflict and experienced interethnic violence to re-build broken social ties and mutual trust. Trying to answer that question we started the training-project "Encouragement of interreligious and interethnic tolerance during the resettlement of returnees" (Čorkalo and Kamenov, 1999). Participants are mental health professionals, paraprofessionals, humanitarian volunteers and community leaders from both sides, Croats and Serbs. The purpose of the project is threefold: educational purpose is accomplished by teaching participants about possible sources of conflicts and conflict resolution, about nature of national stereotypes and prejudice and their influence on human behavior. The experiential goal is achieved through workshops which enables participants to recognize their own prejudice and obstacles they face with in the process of reconciliation in the local communities. Furthermore, helpers from the both sides have the opportunity to interact and to benefit from learning more about each others perspective. We believe that specific knowledge and skills participants have acquired during the workshops would have an impact in their everyday work. In this respect third purpose of the project could be accomplished - an influence on the societal level and possibility to induce changes of ethnic attitudes and behaviors among returnees. The emphasis of the project is put on the ways of encouragement of interethnic and interreligious tolerance as a precondition for peaceful co-existence and reconciliation.
The project is based on the assumption that helping professionals from both sides have an important role in their local communities. There are several reasons which support this assumption: many of helpers were directly involved in psychosocial programs for refugees and internally displaced persons and they are perceived among returnees as highly reliable and trustworthy persons. Some of them were also displaced persons and this kind of "firsthand experience" additionally fosters their credibility in the resettlement communities. Since they continue psychosocial work in their local communities, they have an opportunity to help people to re-build social structure and to influence on the process of building sustainable peace and reconciliation.
Projekt MZOS
ENG